Time-expanded phase-sensitive optical time-domain reflectometry - Miguel Soriano-Amat; Hugo F. Martins; Vicente Durán; Luis Costa; Sonia Martin-Lopez; Miguel Gonzalez-Herraez; María R. Fernández-Ruiz (Light: Science & Applications, 2021)
Abstract Phase-sensitive optical time-domain reflectometry (ΦOTDR) is a well-established technique that provides spatio-temporal measurements of an environmental variable in real time. This unique capability is being leveraged in an ever-increasing number of applications, from energy transportation or civil security to seismology. To date, a wide number of different approaches have been implemented, providing a plethora of options in terms of performance (resolution, acquisition bandwidth, sensitivity or range). However, to achieve high spatial resolutions, detection bandwidths in the GHz range are typically required, substantially increasing the system cost and complexity. Here, we present a novel ΦOTDR approach that allows a customized time expansion of the received optical traces. Hence, the presented technique reaches cm-scale spatial resolutions over 1 km while requiring a remarkably low detection bandwidth in the MHz regime. This approach relies on the use of dual-comb spectrometry to interrogate the fibre and sample the backscattered light. Random phase-spectral coding is applied to the employed combs to maximize the signal-to-noise ratio of the sensing scheme. A comparison of the proposed method with alternative approaches aimed at similar operation features is provided, along with a thorough analysis of the new trade-offs. Our results demonstrate a radically novel high-resolution ΦOTDR scheme, which could promote new applications in metrology, borehole monitoring or aerospace.